2019
DOI: 10.1111/acel.12998
|View full text |Cite
|
Sign up to set email alerts
|

New label‐free automated survival assays reveal unexpected stress resistance patterns during C. elegans aging

Abstract: Caenorhabditis elegans is an excellent model for high‐throughput experimental approaches but lacks an automated means to pinpoint time of death during survival assays over a short time frame, that is, easy to implement, highly scalable, robust, and versatile. Here, we describe an automated, label‐free, high‐throughput method using death‐associated fluorescence to monitor nematode population survival (dubbed LFASS for label‐free automated survival scoring), which we apply to severe stress and infection resistan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…Resistance to heat and oxidative stress was assessed by the label-free automated survival scoring (LFASS) approach, which relies on time-lapse measurements of blue death fluorescence (λ ex = 360 nm, λ em = 435 nm) [ 44 ]. For both assays, approximately 200 worms were placed per well in a clear-bottom 96-well plate, supplemented with previously frozen OP50 to avoid starvation.…”
Section: Methodsmentioning
confidence: 99%
“…Resistance to heat and oxidative stress was assessed by the label-free automated survival scoring (LFASS) approach, which relies on time-lapse measurements of blue death fluorescence (λ ex = 360 nm, λ em = 435 nm) [ 44 ]. For both assays, approximately 200 worms were placed per well in a clear-bottom 96-well plate, supplemented with previously frozen OP50 to avoid starvation.…”
Section: Methodsmentioning
confidence: 99%
“…The literature linking stress, innate immunity, and aging in C. elegans has long supported a simple model that stress resistance and innate immunity are linked, and that the two are inversely correlated with age [33,34]. Although recent, more detailed findings have suggested that it is not quite this simple [35], a strong correlation between stress and pathogen resistance remains. Indeed, it has been clearly demonstrated that stress-inducing compounds can promote pathogen resistance, albeit with some adverse effects on the host.…”
Section: The Activity Of Lk Molecules Is Not Mediated By Conventionalmentioning
confidence: 99%
“…The literature linking stress, innate immunity, and aging in C. elegans has long supported a simple model that stress resistance and innate immunity are linked and that the two are inversely correlated with age ( 34 , 35 ). Although recent, more detailed findings have suggested that it is not quite this simple ( 36 ), a strong correlation between stress and pathogen resistance remains. Indeed, it has been clearly demonstrated that stress-inducing compounds can promote pathogen resistance, albeit with some adverse effects on the host.…”
Section: Resultsmentioning
confidence: 99%